Young Male with Rash and Decreased Vision - Erfan, Muhammad (International Journal of Pathology, 2018)
Pseudoxanthoma elasticum is a rare disorder of degeneration and calcification of the elastic fibres. It is believed to be a multisystem disorder with involvement particularly of the skin, eyes and the peripheral circulation. Here we present a case with typical features of pseudoxanthoma elasticum. Confirmation of the disease was based on typical histopathological changes on skin biopsy, positive gene analysis and on findings of fundoscopy.